1975
DOI: 10.1007/bf00353240
|View full text |Cite
|
Sign up to set email alerts
|

Acrylonitrile biotransformation in rats, mice, and chinese hamsters as influenced by the route of administration and by phenobarbital, SKF 525-A, cysteine, dimercaprol, or thiosulfate

Abstract: Female wistar rats, conventional albino mice, and Chinese hamsters were given a single dose of acrylonitrile, 0.5 or 0.75 mM/kg body weight. The elimination in the urine of thiocyanate, which is the main metabolite of acrylonitrile, indicated a decreasing proportion of biotransformation after oral (over 20%), intraperitoneal, or subcutaneous (2 to 5%), and intravenous (1%) administration in rats. Oral administration of acrylonitrile in hamsters and mice was also followed by higher biotransformation than intrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…This further suggested that multiple P450s may be involved in the metabolism of AN to cyanide (Mostafa et al, 1999). Earlier studies showed that inducers (phenobarbital) and inhibitors (SKF 525A) of P450 enzymes had no effect on thiocyanate excretion in animals (Gut et al, 1975). In contrast, recent studies showed that CEO-derived mercapturic acids, which are normally identified in the urine of AN-treated mice, were not detectable in the urine of CYP2E1-null mice treated with this chemical (Sumner et al, 1999;Ghanayem et al, 2000).…”
Section: Acrylonitrile (Anmentioning
confidence: 99%
“…This further suggested that multiple P450s may be involved in the metabolism of AN to cyanide (Mostafa et al, 1999). Earlier studies showed that inducers (phenobarbital) and inhibitors (SKF 525A) of P450 enzymes had no effect on thiocyanate excretion in animals (Gut et al, 1975). In contrast, recent studies showed that CEO-derived mercapturic acids, which are normally identified in the urine of AN-treated mice, were not detectable in the urine of CYP2E1-null mice treated with this chemical (Sumner et al, 1999;Ghanayem et al, 2000).…”
Section: Acrylonitrile (Anmentioning
confidence: 99%
“…29) This is very interesting because thalidomide is virtually non-toxic to rats when given orally (PO). Intraperitoneal (IP), administration however, commonly associated with "first-pass" hepatic metabolism, 30) recapitulates the teratogenic effect of thalidomide in rats. 31) Kenyon et al 19) also showed that thalidomide given IP was effective as an anti-angiogenic agent in the mouse corneal model, whereas thalidomide given PO was inactive.…”
mentioning
confidence: 99%
“…This was undoubtedly due to a significant competing reaction for AN in blood, namely the reaction of AN with the sulfhydryl groups of hemoglobin. Hemoglobin is known to be highly reactive with AN (Fennell et al, 1991b;Ahmed et al, 1983;Gut et al, 1975) and this could explain the observation that covalent binding of AN to blood proteins was three to four times higher than any other tissue (Fig. 4).…”
Section: Discussionmentioning
confidence: 97%